Komunikasi Corporate Social Responsibility dalam Pilar Kesehatan di Metro TV (Studi pada Program CSR Operasi Katarak Gratis) - Hendrayani, Yani; Monalisa , Sherly Maria (KOMUNIKA, 2025)
Corporate social responsibility requires companies to communicate with their stakeholders. Therefore, corporate social responsibility (CSR) communication is as important as CSR programs. This research aims to find out whether Metro TV conducts corporate social responsibility (CSR) communication and how corporate social responsibility (CSR) communication on the health pillar of the free cataract surgery program. This research uses descriptive qualitative method. Referring to stakeholder theory and the concept of corporate social responsibility (CSR). Data were collected through in-depth interviews with two key informants, namely the CSR & Community Relations Manager and the staff of Metro TV. Informants consisted of Perdami public relations staff as well as two participants of the free cataract surgery program. The results showed that Metro TV communicates corporate social responsibility (CSR) in the health pillar of the free cataract surgery program through various publications containing CSR messages of Metro TV's initiatives and commitments related to the free cataract surgery program channeled in various media such as press releases, Metro TV platforms, news media, and social media. Metro TV's corporate social responsibility (CSR) communication in the health pillar of the free cataract surgery program uses CSR communication strategies classified by Morshing and Schultz, namely stakeholder theory consisting of stakeholder information strategies, stakeholder response strategies, and stakeholder engagement strategies.